Pengaruh Hukum Adat terhadap Kebijakan Reformasi Agraria di Indonesia - Hafizh Naufalian; Moh. Dandi Putra Susendi; Olivia Zahra Yuwono (Majelis: Jurnal Hukum Indonesia, 2025)
A Customary law is an unwritten legal system that has lived and developed in Indonesian society since before the arrival of Western law. This article reviews the role of customary law as part of Indonesia's national legal system, focusing on its relevance and existence in the modern era. Through a qualitative approach with a literature study method, this article discusses how customary law continues to exist amid the challenges posed by globalisation and the development of positive law. The author highlights the importance of preserving the values of customary law as it reflects cultural identity as well as a form of recognition of the rights of customary law communities. The results of the discussion show that although customary law is not systematically recorded, it has an important role in dispute resolution, as well as regulating the social life of the community. Therefore, the integration of customary law into the national legal system needs to be improved to create contextual justice rooted in local culture and values.